Public theology and institutional economics : all is economy - Hoogen, T. van den (Cambridge Scholars Publishing, 2019)
This book shows why, in our modern society, many important questions in our public debates urge for attention to be given to questions about economy, and why religious thinking gives unexpectedly relevant perspectives on these. Neither economy nor religion is a private matter. Our daily life and personal decisions about lifestyle are marked by our public choices and attitudes. As we are actually part of complex and disturbing processes in an information society, our daily lives are changing in rapid ways. Beginning with a discussion of what public theology is actually about, the text moves on t.